Analisis MPN E. Coli dan Total Coliform pada Air Bersih di SPPG Kabupaten Malang - Nuralya Yuniarwati; Rusmini (Unesa Journal of Chemistry, 2026)
Clean water is water that meets the requirements for daily activities. The quality of clean water can be determined chemically, physically, and biologically. The purpose of this study was to determine the number of Coliform and E. coli bacteria in clean water samples. The method used is the MPN (Most Probable Number) method. The sample in this study was total sampling, namely the entire population was made into a research sample of 5 samples. There were 2 Coliform examination results that met the standard, namely SPPG A (0 MPN/100 ml) and SPPG E (0 MPN/100 ml). 3 samples did not meet the standard, namely SPPG B (> 1600 MPN/100 ml), SPPG C (6.8 MPN / 100 ml), SPPG D (39 MPN/100 ml). In the E. coli examination, there were 2 results that met the standard, namely SPPG A (0 MPN / 100 ml) and SPPG E (0 MPN/100 ml). Three results that did not meet the standards were SPPG C (350 MPN/100 ml), SPPG D (6.8 MPN/100 ml), SPPG E (4.5 MPN/100 ml). Based on the results of the clean water examination conducted, with a total of 5 samples, it showed that 2 samples met biological requirements.